Nitric Oxide Synthase Inhibition Protects Against RotenoneInduced Neurodegeneration in vivo - Abdel-Salam, Omar M.E.; Youness, Eman R.; Omara, Enayat A. (Journal of Neurology and Epidemiology, 2022)
Neuropathologic and motor features of Parkinson’s disease can be induced in rodents by the pesticide rotenone. In this study, we aimed to determine whether nitric oxide synthase inhibition by NG-nitro-L-arginine methyl ester (L-NAME) could prevent neurodegeneration and biochemical changes induced by rotenone in rat brain. For this purpose, rats received subcutaneous injections of rotenone (1.5 mg/kg) every other day for two consecutive weeks and were treated at the same time with L-NAME at doses of 10 or 20 mg/kg, intraperitoneally. Oxidative stress indictors, malondialdehyde, reduced glutathione, and nitric oxide as well as paraoxonase-1 (PON-1) activity in brain, and the concentration of the antiapoptotic protein B cell/lymphoma-2 (Bcl2) in striatum were determined. Motor strength and coordination was assessed using wire hanging and stair tests. Neuronal degeneration was evaluated using hematoxylin & eosin-stained brain sections. Results: L-NAME reduced, in a dose-dependent manner the increase in lipid peroxidation (malondialdehyde) and nitric oxide and restored reduced glutathione levels in brain of rotenone-treated rats. Additionally, L-NAME prevented the inhibition of paraoxonase-1 activity and the decrease in Bcl2 concentration induced by the pesticide. It also prevented motor impairments in a dose-dependent manner. Furthermore, L-NAME treatment ameliorated the neurodegenerative effects of rotenone, as shown by the decrease in degenerated neurons in striatum and cerebral cortex. The results of the present study suggest that rotenone mediates its neurotoxic effects, at least in part by nitric oxide-dependent mechanisms.